Heavy-metal remediation by a fungus as a means of production of lead and cadmium carbonate crystals - Sanyal, A.; Rautaray, D.; Bansal, Vipul; Ahmad, Absar; Sastry, Murali (Langmuir, 2005)
We show here that reaction of the fungus, Fusarium oxysporum, with the aqueous heavy-metal ions Pb2+ and Cd2+ results in the one-step formation of the corresponding metal carbonates. The metal carbonates are formed by reaction of the heavy-metal ions with CO2 produced by the fungus during metabolism and thus provide a completely biological method for production of crystals of metal carbonates. The PbCO3 and CdCO3 crystals thus produced have interesting morphologies that are shown to arise because of interaction of the growing crystals with specific proteins secreted by the fungus during reaction. An additional advantage of this approach is that the reaction leads to detoxification of the aqueous solution and could have immense potential for bioremediation of heavy metals. Under conditions of this study, the metal ions are not toxic to the fungus, which readily grows after exposure to the metal ions.

Halide ion controlled shape dependent gold nanoparticle synthesis with tryptophan as reducing agent: enhanced fluorescent properties and white light emission - Kasture, Manasi; Sastry, Murali; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2010)
We report the synthesis of Au nanoparticles in presence of two surfactants cetyltrimethyl ammonium chloride (CTAC) and cetyltrimethyl ammonium bromide (CTAB) by reducing Au(3+) ions with tryptophan. Interestingly, triangular shaped particles were seen to form in presence of CTAB, while spherical nanoparticles resulted with CTAC. The highlight of this result is the white light emission from the Au triangles obtained when CTAB is used. These results are supported by lifetime measurements and fluorescence. (C) 2009 Elsevier B. V. All rights reserved.